Awareness, knowledge, and practice towards medication overuse headache in Thailand: A university hospital-based survey in residency training programs - Prakit Anukoolwittaya; Thanakit Pongpitakmetha; Akarin Hiransuthikul; Sekh Thanprasertsuk; Wanakorn Rattanawong (SAGE Publishing, 2024)
Background Medication overuse headache (MOH) presents a considerable challenge in patient care, with physicians playing a critical role in its prevention and management. However, awareness, knowledge, and practices regarding MOH among physicians are often found to be inadequate. Methods A cross-sectional study was conducted at King Chulalongkorn Memorial Hospital to investigate the awareness, knowledge, and practices concerning MOH among residents from family medicine, internal medicine, and neurology specialties. Participants were surveyed using an internet-based questionnaire. Results Of the 130 residents, 70 participated in the study. Ten percent were unaware that analgesics could exacerbate headaches, a finding particularly notable among family medicine residents. Furthermore, 11.4% of participants were uncertain about the classification of MOH, while 31.4% and 44.3% were uncertain about the frequency with which the use of simple analgesics and migraine-specific drugs could lead to MOH, respectively. This uncertainty was prevalent among residents in internal medicine and family medicine. Additionally, 22.9% of participants, especially those in internal medicine, prescribed opioids for abortive treatment in migraine patients. Residents in neurology generally performed better across various aspects compared to those in other specialties. Conclusion The study highlights a significant gap in the awareness, knowledge, and practices regarding MOH, particularly in non-neurology residency programs. Addressing these issues may require continuous medical education utilizing a multifaceted approach, encompassing undergraduate courses, postgraduate training, and public outreach.